The Decision Support System In Land Selection For Rubber Tree Planting Using The Moora Method - Eliza Amanda (International Journal of Health Engineering and Technology, 2022)
Decision support system in the selection of land for rubber tree planting in order to minimize time and help PT. GERGAS UTAMA to determine quality land so as to increase rubber productivity. This method also has a good level of selectivity because it can determine the purpose of conflicting criteria. Where the criteria can be profitable (benefit) or unfavorable (cost). The selection of the right rubber area will certainly affect the production of rubber plants. In the process of selecting the right rubber area, of course, there are several criteria that will determine whether or not a land is suitable for producing rubber plantations such as temperature, rainfall, drainage, soil texture and so on. PT Gergas Utama has difficulty in the process of selecting this land because the selection process is still done manually which of course will take longer so that it becomes ineffective and affects the productivity of the rubber plant.Based on the description above, it is necessary to build a decision support system in the selection of land for rubber tree planting in order to minimize time and help PT Gergas Utama to determine quality land so as to increase rubber productivity. In the development of this decision support system, the MOORA (Multi-Objective Optimization by Ratio Analysis) method is used, which is a method that has a level of flexibility and ease of understanding in separating the subjective part of an evaluation process into decision weight criteria with several decision-making attributes. The program used in the development of the Decision Support System is PHP for a web-based system and MySQL as a database management system. The results ofthis program indicate that the Decision Support System for the selection of land for planting rubber trees can be utilized by PT. GERGAS UTAMA is the rubber plantation sector in selecting the best land for planting. The results of the ranking calculation from the MOORA (Multi-Objective Optimization by Ratio Analysis) method from a total of 10 rubber land planting locations with a value of 0.369, the result of the sum of the criteria weights being the highest. the best has the highest value of 0.369.